Haematologic-related malignancy-induced eosinophilic dermatoses (He Remained): A narrative review - Bikash Ranjan Kar; Akash Agarwal (Wolters Kluwer Medknow Publications, 2022)
He remained(Hematologic Related Malignancy- induced Eosinophilic dermatoses) is a new eponym introduced to describe a dermatoses previously described under several terminologies such as eosinophilic dermatoses of haematological malignancy, exaggerated arthropod bite reactions, insect bite-like reactions and T-cell papulosis associated with B-cell malignancies. This chronic relapsing remitting disease has a pleomorphic presentation mimicking a variety of dermatological conditions. The underlying pathophysiology is however poorly understood. It is a paraneoplastic phenomenon hence an underlying haematological malignancy must always be looked for. Response to conventional modalities of treatment such as oral corticosteroids is rapid and satisfactory. Other newer modalities are also in the pipeline. In this manuscript, we present a narrative review of this recently described entity with data identified via a search on 27 September, 2021 in PubMed, EMBASE and MEDLINE using the term 'Eosinophilic dermatoses of haematological malignancy' AND 'Hematologic related malignancy-induced eosinophilic dermatoses'. A total of 67 cases reported in the literature from the year 2012 onward have been included. The literatures pertaining to insect bite-like reactions and exaggerated insect bite hypersensitivity have been excluded in this review.